The Creation of an Animal Component-Free Medium for Mammalian Cells in 2D and 3D Microenvironments - Mogilever, Nicolette Bianca (Université d'Ottawa / University of Ottawa, 2024)
In modern biotechnology, the ability for researchers to grow cells in laboratory settings (in vitro) allows them to harness the power of cell culture science to study diseases, develop new technologies, and better understand biological processes. Cell culture medium is the vehicle that supplies cells in vitro with the nutrients necessary for maintaining normal cell growth, metabolism, and function. Culture medium often contains added supplements from animal sources that provide a complex mixture of hormones, growth factors, lipids, and other components required for many mammalian cells to survive outside of their native environments. Specifically, fetal bovine serum (FBS) is the most widely used serum supplement for mammalian cell culture, yet its limitations and drawbacks have prompted a search for alternative formulations. The disadvantages of using animal-based supplements such as FBS are highlighted when investigations into their manufacture demonstrate unethical means of harvesting, and analyses of different samples show inconsistencies. While alternative serum-free (SF) options exist, they are often cell-type specific, may contain residual animal-derived components, and are usually developed for non-universal conditions. There is continual progress being made in this field, yet it needs to be built upon by fabricating SF formulations that can grow multiple cell types while remaining fully animal component-free (ACF). This thesis addresses the need for an ACF substitute for FBS in mammalian cell culture by focusing on the development of a medium formulation through empirical experimentation. By identifying essential components for cell growth and function from the literature, various concentrations of these components were systematically tested to evaluate their impact on cell viability and morphology in different types of microenvironments. Diverse microenvironments for cell cultures can be carried out depending on the application, including traditional two-dimensional (2D) growth on Petri dishes, but also three-dimensional (3D) culture on complex scaffolds or in suspension vessels. To explore the universal nature of the medium formulation developed in our work, three distinct investigations were undertaken. In our first investigation, we assess the effectiveness of the optimized formulation on cells grown in 2D conditions on Petri dishes (Chapter 2). In our second investigation, we slightly modify the formulation to cater to another distinct cell type which grows in suspension cultures. Here, we examine our formulation's effectiveness as the suspensions are cultivated in spinning flasks (Chapter 3). In our third investigation, we assess the efficacy of the formulation in supporting cell growth for the same cell types from our first investigation, but cultured on plant-derived 3D scaffolds, as opposed to flat, 2D Petri dishes (Chapter 4). The results demonstrate that the formulated medium can support robust cell growth and preservation of morphology across diverse cell types, comparable to the performance of an FBS-based medium. While further research is needed to extend these findings to other cell types and applications, this work highlights the importance of specific media components in mammalian cell culture and provides a framework for SF medium development in multiple microenvironments. A review on the fundamentals of cell culture, mechanisms of cell growth in vitro, medium components, serum alternatives, 2D vs 3D microenvironments, and their applications serves as the introductory chapter to this thesis (Chapter 1).
Keywords: fetal bovine serum; FBS; serum; culture medium; cell culture; animal-free; alternatives; plant scaffolds